IMPLEMENTATION OF A BLENDED LEARNING MODEL ON A SOCIAL SCIENCE SUBJECT AT VIII GRADES IN SMP NEGERI 1 AIR BLACK DISTRICT LAMPUNG BARAT ACADEMIC YEAR 2021/2022 - Ardila, Evi; Pargito; Utami, Dian; Zulkarnain (Journal Learning Geography, 2023)
This study aims to find out how the implementation of the blended learning model in class VIIIA SMPN 1 Air Hitam learning social studies. The research method used a qualitative approach and this research was conducted at SMPN 1 Air Hitam. Data collection techniques with interviews, observation and documentation. While the sampling technique used purposive sampling aimed at the school principal, social studies teacher and several students of SMPN 1 Air Hitam. Test the validity of the data with technical triangulation and data analysis with interaction analysis whose steps start from data collection, data reduction, data presentation and verification. The results of the research on the implementation of the blended learning learning model have been carried out starting from lesson planning, implementing learning according to the blended learning syntax, namely seeking of information, acquisition of information and shyentesizing of knowledge which is carried out both in online and face-to-face learning. Assessment of blended learning includes assessment of attitudes, knowledge and skills. The conclusion of this study is that the implementation of the blended learning model in class VIII A can be seen through planning activities that the teacher has prepared learning tools, schedules and teaching materials. The implementation activities are in accordance with the blended learning syntax. The assessment activities are carried out face-to-face and online.